New Insights into the Adsorption Mechanism of Vanadium Through Quaternary Ammonium Salt-Functionalized SiO2: Synergistic Experiments Utilizing Energy Decomposition Analysis - Qiang Fu; Jianhua Tian; Jinjun Yang; Jie Wang; Meitong Li; Gangzhen Jiao; Yuhong Xie; Wenjiao Yuan; Cuihong Wang (Molecules)
Introducing organic functional groups to adsorbent surfaces enhances vanadium adsorption, an effective strategy for vanadium enrichment. In a quest for a profounder comprehension of the above adsorption mechanism, this study synthesized five types of quaternary ammonium salt-functionalized silica (QAS-SiO2) and investigated the influence of functional groups, pH values, contact time, and temperature on vanadium (V) adsorption. The results indicated that the optimal QAS-SiO2 (SiO2@DMOA) achieved a vanadium adsorption rate of 99.40% and a maximum adsorption capacity of 39.16 mg g−1. SiO2@DMOA exhibited favorable adsorption selectivity for V over chromium (Cr), with a maximum separation factor (βV/Cr) of 135.42 at pH 3.3. SiO2@DMOA maintained efficient adsorption performance over five repeated cycles. A fusion of adsorption trials with energy decomposition analysis (EDA) tentatively unveiled that both chemical bonds and non-bonding interactions contributed to the interaction energy between organic functional groups and vanadium. Among them, chemical bonds accounted for 80.26%, while non-bonding interactions accounted for 19.74%. Based on EDA analysis, the interaction characteristics of different structural quaternary ammonium salts with vanadium in adsorption and extraction processes are discussed. Additionally, steric hindrance, the charge of the vanadium species, polarizability, and solvation effects, all played significant roles in the adsorption process.